2016
DOI: 10.1155/2016/9265948
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Nanoindentation of Cu/Au Thin Films at Different Temperatures

Abstract: Two methods, deposition method and ideal modeling based on lattice constant, are used to prepare three modulation periods’ (1.8 nm Cu/3.6 nm Au, 2.7 nm Cu/2.7 nm Au, and 3.6 nm Cu/1.8 nm Au) thin films for nanoindentation at different temperatures. The results show that the temperature will weaken the hardness of thin films. The deposition method and the formation of coherent interface will result in a lot of defects in thin films. These defects can reduce the residual stress in the thin films which is caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Two theoretical guidelines for the class mechanism explain the evolution mechanism of 3C-SiC plastic deformation. Elchin M et al [ 12 , 13 ] studied the change in the surface of 3C-SiC particles with temperature and the heating rate, determined the specific heat capacity and Gibbs free energy at different heating rates, which has important reference significance for the field of 3C-SiC thermal processing, and studied the nanoindentation of Cu/Au thin films at different temperatures by the deposition method and ideal modeling method based on lattice constant, then visualized and analyzed the lattice structure based on open software Ovito. It was found that the hardness of the film weakened with the increase in temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Two theoretical guidelines for the class mechanism explain the evolution mechanism of 3C-SiC plastic deformation. Elchin M et al [ 12 , 13 ] studied the change in the surface of 3C-SiC particles with temperature and the heating rate, determined the specific heat capacity and Gibbs free energy at different heating rates, which has important reference significance for the field of 3C-SiC thermal processing, and studied the nanoindentation of Cu/Au thin films at different temperatures by the deposition method and ideal modeling method based on lattice constant, then visualized and analyzed the lattice structure based on open software Ovito. It was found that the hardness of the film weakened with the increase in temperature.…”
Section: Introductionmentioning
confidence: 99%
“…To better describe the interactions between the Cu and Sn atoms, the modified embedded atom method (MEAM) interatomic potential was used. The MEAM interatomic potential has been fully discussed in references [21,22], and it has provided good results in simulating the mechanical properties [15,23], defect formation [24][25][26] and diffusivity [27,28] of both solid and liquid materials; thus, it will not be introduced here again.…”
mentioning
confidence: 99%